The main asteroid belt: The primary source of debris on comet-like orbits - Shober, Patrick M.; Sansom, Eleanor; Bland, Phil; Devillepoix, Hadrien; Towner, Martin; Cupak, Martin; Howie, Robert; Hartig, Benjamin; Anderson, S.L. (2021)
Jupiter-family comets (JFCs) contribute a significant amount of debris to near-Earth space. However, telescopic observations of these objects seem to suggest that they have short physical lifetimes. If this is true, the material generated will also be short-lived, but fireball observation networks still detect material on cometary orbits. This study examines centimeter-to-meter-scale sporadic meteoroids detected by the Desert Fireball Network from 2014 to 2020 originating from JFC-like orbits. Analyzing each event's dynamic history and physical characteristics, we confidently determined whether they originated from the main asteroid belt or the trans-Neptunian region. Our results indicate that <4% of sporadic meteoroids on JFC-like orbits are genetically cometary. This observation is statistically significant and shows that cometary material is too friable to survive in near-Earth space. Even when considering shower contributions, meteoroids on JFC-like orbits are primarily from the main belt. Thus, the presence of genuine cometary meteorites in terrestrial collections is highly unlikely.